2013
DOI: 10.14258/turczaninowia.16.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Karyological Studies on Siberian Species of Nitraria L. (Nitrariaceae)

Abstract: Аннотация. Представлены результаты кариологического изучения двух сибирских видов Nitraria (N. sibirica и N. schoberi) из разных популяций Южной Сибири. Кариотипы этих видов характеризуются миксо-плоидией и вариабельностью хромосомных чисел при основном числе х=12. У N. sibirica чаще встречается диплоидное число хромосом 2n=24, у N. schoberi преобладает тетраплоидное число 2n=48.Ключевые слова: селитрянка сибирская, селитрянка Шобера, число хромосом, кариотип. Summary. Results of karyological study of two Nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
5
0
2
Order By: Relevance
“…These species cannot always be distinguished; the herbarium specimen identification is difficult [4][5]. Attempts to resolve the taxonomy of Siberian species of the genus Nitrаria have been made based on karyological [6], morphological [7] characters, but molecular markers have several advantages over them, demonstrating significant differences at the genetic level without environmental factor participation. The work objective is a comparative analysis of the nucleotide variability of the ITS2 region and identification of its significance in the taxonomy of the genus Nitrаria species.…”
Section: Introductionmentioning
confidence: 99%
“…These species cannot always be distinguished; the herbarium specimen identification is difficult [4][5]. Attempts to resolve the taxonomy of Siberian species of the genus Nitrаria have been made based on karyological [6], morphological [7] characters, but molecular markers have several advantages over them, demonstrating significant differences at the genetic level without environmental factor participation. The work objective is a comparative analysis of the nucleotide variability of the ITS2 region and identification of its significance in the taxonomy of the genus Nitrаria species.…”
Section: Introductionmentioning
confidence: 99%
“…The most likely explanation of variability of DNA content in N. schoberi seeds is a widespread aneuploidy in the genus Nitraria [16]. Karyological study showed that there was no certain number of chromosomes in N. schoberi cells, only the most frequently encountered 2n=4x=48 [3,4,17]. In a number of works was noted influence of aneuploidy on the genome size and shown that the method of cytometry was sensitive and informative enough for detection of that phenomenon [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Nitraria L. species are typical halophytes, their populations are often small and isolated since they are restricted to intrazonal communities. Nitraria schoberi L. Is the most polymorphic species, it is characterized by mixoploidy and variability of chromosome numbers which may be one of the factors of plant adaptation to habitat extreme conditions [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Материалом для исследований явились семена, собранные с дикорастущих и культивируе-мых растений. Изучение наборов хромосом проводилось на давленых препаратах по стандартной методике (Barykina et al, 2004;Muratova et al, 2013), адаптированной к нашим объектам. Семена проращивались при комнатной температуре, либо (в случае необходимости) стратифицировались в холодильнике при температуре +2 ºС в течение 1-6 месяцев.…”
Section: материалы и методикаunclassified